Experimental Investigation on the Role of Clays in Low Salinity Water Flooding - Wei, Xuemei; Zhang, Yanyu; Jiang, Wenchao; Wang, Zhao; Li, Xiaojun; Wu, Feipeng (Frontiers in Energy Research, 2020)
Clay minerals are regardedn important factor affecting the results of low salinity water (LSW) flooding. However, most researchers put great attention on microscopic properties, only few of them investigated the influence of clay minerals by sandpack flooding experiments. This paper quantifies the effects of the clay minerals of in LSW flooding with the artificial sandpack samples. We used three kinds of sandpack samples (100% quartz sand; 90%/10% quartz sand/kaolinite or montmorillonite) and heavy oil in the LSW flooding process. Montmorillonite has optimal LSW’s salinity. The best salinity of Na+ is between 1000 mg/L and 5000 mg/L, and Ca2+ is between 500 mg/L and 1000 mg/L. As for kaolinite, the lower the LSW’s salinity, the results are better. In addition, using CaCl solution floods montmorillonite has better result and NaCl solution floods kaolinite has better result. Respect of flooding modes, the continuous injection of high-low salinity water is more effective, but the LSW flooding is better considering the economy and time cost.